1993
DOI: 10.1097/00006842-199311000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and neuroendocrine responses to extended laboratory challenge.

Abstract: The purpose of this study was to examine the effects of a 2-hour laboratory challenge on heart rate, blood pressure, catecholamines, and cortisol; and investigate the contribution of the physical act of speaking on both neuroendocrine and cardiovascular measures. Using a within-subjects design, 14 subjects were tested individually during two separate laboratory sessions. During one session, subjects engaged in two cognitively demanding tasks for 2 hours. During the other session, subjects executed the verbal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…In addition, the response of the adrenal cortex to ACTH stimulation was significantly diminished in group H+HTG. These findings are in agreement with the suggestion that hypertension is associated with altered neuroendocrine responsiveness to stress situations, 16,25,26 especially with the hypothalamic-pituitary-suprarenal axis in the pathogenesis of the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the response of the adrenal cortex to ACTH stimulation was significantly diminished in group H+HTG. These findings are in agreement with the suggestion that hypertension is associated with altered neuroendocrine responsiveness to stress situations, 16,25,26 especially with the hypothalamic-pituitary-suprarenal axis in the pathogenesis of the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…In a well-designed, controlled investigation, McCann et al [46]studied a sample of 14 healthy men, aged 21–49 years (mean age 31.8 years). The Stroop color-word interference test was administered 8 times during the first hour of stress session, whereas a paced auditory serial addition task was administered 5 times during the second hour.…”
Section: The Psychoendocrine Reaction To Laboratory Stressorsmentioning
confidence: 99%
“…Since the experiment was carried out in the morning, the observed decrease in cortisol levels corresponds to established circadian patterns. Norepinephrine levels increased significantly during both sessions, with higher levels during the stress session than during the control one, although the difference did not reach statistical significance [46]. These findings clearly illustrate that the degree of cognitive effort required for a laboratory task represents an important modulator of the psychoendocrine response.…”
Section: The Psychoendocrine Reaction To Laboratory Stressorsmentioning
confidence: 99%
“…Also, Hidaka et al (19) used a long-term stressor and found notable haemodynamic changes and little EMG change in the masseter muscle. Mental arithmetic, such as the Paced Auditory Serial Addition Task (PASAT) (20), is well recognized to induce circulatory reactions resembling the classical defense reaction and has been widely utilized as a laboratory psychological stressor (21).…”
Section: Introductionmentioning
confidence: 99%